Zugang zu Sozialleistungen in Taiwan - Tsai, Ya-Chu (Studien aus dem Max-Planck-Institut für Sozialrecht und Sozialpolitik, 2021)
This dissertation examines the question of whether the non-systematic or non-purpose-related benefit requirements in social law are in accordance with the Constitution in Taiwan. Access to social benefits is opened when the legal requirements are fulfilled. However, not all these requirements are system-related or purpose-oriented. In such cases, access to social benefits may be restricted or even blocked. Such benefit requirements are often found in Taiwanese social law, especially foreigners are involved. In this research, the constitutionality of the social benefit requirements will be examined.